Impact of lifestyle modifications on morbidities associated with polycystic ovarian syndrome - Mehrotra, Ragini; Chaudhary, Richa; Saxena, Somya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The study aimed to systematically review the efficacy of long-term (6 to 9 months) lifestyle modifications in the form of dietary modifications, weight loss interventions, and psychosocial and behavioural changes. Methods: This observational study was done on 110 women with PCOS-like features for one year. Personal and menstrual history was recorded. General and systemic examination was done. Routine investigations of blood and urine were done. The level of hormones was evaluated. USG of the lower abdomen and pelvis was also done. The data were recorded and analysed statistically. Results: Significant difference was observed in all parameters before and after lifestyle and behavioral modifications. Conclusions: Lifestyle interventions may improve weight and BMI in women with PCOS. Women who underwent lifestyle modifications significantly improved menstrual and reproductive function. We considered adopting a healthy lifestyle with a low-calorie diet and physical exercise that will generate weight loss.